THE SIGNIFICANCE AND PLACE OF USING NATIONAL VALUES IN THE EDUCATION OF THE YOUNG GENERATION - Parvina Kholikova Abdumalik kizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information about the importance and role of using national values in the education of the young generation.